Fostering inclusive water use and productivity in South Africa and Malawi through VIA’s Chameleon Water Sensor - Opola, Felix Ouko; Dyer, S.; Garcia Andarcia, Mariangel (2024)
While digital tools and services present an opportunity to address some of the critical challenges facing food and water systems, concerns remain over large groups of people, such as women, elderly people, or people with little formal education, who may be excluded from the development, use, and benefit of digital innovation. In this report we present the outcome of a study that was conducted to assess whether a digital innovation that provides an irrigation service in many African countries was socially inclusive. The assessment was done with the multi-dimensional digital inclusivity index, a tool that is being developed for assessing digital inclusiveness across various dimensions in food, land, and water systems.